2017
DOI: 10.1002/14651858.cd004735.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Planned early birth versus expectant management for women with preterm prelabour rupture of membranes prior to 37 weeks' gestation for improving pregnancy outcome

Abstract: With the addition of five randomised controlled trials (2927 women) to this updated review, we found no clinically important difference in the incidence of neonatal sepsis between women who birth immediately and those managed expectantly in PPROM prior to 37 weeks' gestation. Early planned birth was associated with an increase in the incidence of neonatal RDS, need for ventilation, neonatal mortality, endometritis, admission to neonatal intensive care, and the likelihood of birth by caesarean section, but a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 44 publications
5
100
0
8
Order By: Relevance
“…More recently, a Cochrane review of 3617 women explored the effect of planned early delivery versus expectant management for women with PPROM. 43 The authors conclude that in women with PPROM 'with no contraindications to continuing the pregnancy, expectant management with careful monitoring is associated with better outcomes for the mother and baby'. The Cochrane review found no differences between early birth and expectant management in neonatal sepsis or infection.…”
Section: Evidence Level 2+mentioning
confidence: 96%
See 3 more Smart Citations
“…More recently, a Cochrane review of 3617 women explored the effect of planned early delivery versus expectant management for women with PPROM. 43 The authors conclude that in women with PPROM 'with no contraindications to continuing the pregnancy, expectant management with careful monitoring is associated with better outcomes for the mother and baby'. The Cochrane review found no differences between early birth and expectant management in neonatal sepsis or infection.…”
Section: Evidence Level 2+mentioning
confidence: 96%
“…There were no differences in overall perinatal mortality or intrauterine deaths when comparing early delivery with expectant management. Early birth was associated with a higher rate of neonatal death (RR 2.55, 95% CI 1.17–5.56) and need for ventilation (RR 1.27, 95% CI 1.02–1.58) Evidence level 1++ …”
Section: Birthmentioning
confidence: 99%
See 2 more Smart Citations
“…This review (Bond et al, ) aimed to compare the results of planned early birth and expectant management in women who went into premature labour between 24 and 37 weeks gestation following rupture of their membranes. Planned early birth occurs as soon as possible after rupture of membranes, and the methods include induction of labour and caesarean section.…”
Section: Objective/smentioning
confidence: 99%